INTANGIBLE ASPECT OF THE VALUE ADDED - Rima Tamosiuniene; Simona Survilaite (European Scientific Journal, ESJ, 2014)
The most important issue and challenge is to identify and understand concepts and processes that are constantly changing and appearing in almost every company. Implementing and adapting these elements are even more difficult. The processes and procedures are becoming more sophisticated and needs a special handling and knowledge. What is more, moving from tangible aspect to intangible perspective requires effectiveness and quality. Nowadays the concept of value added is important for managers and shareholders in order to make business decisions and to forecast economic situation. Nevertheless, there is still misunderstandings and discrepancies regarding the intangible assets, difference between market value and book value.